(untitled) - USA, AMILUS INC (USA, 1992)
1.Editorial / 2.Books / 3.Advertising y posters / 4.Design / 5.maps and computer graphics / 6.Unpublished work
Incluye indice de ilustraciones pag.242
Keywords: ILUSTRACION